AAV1.NT-3 gene therapy increases muscle fiber diameter through activation of mTOR pathway and metabolic remodeling in a CMT mouse model. Issue 2 (April 2018) - Yalvac, Mehmet; Amornvit, Jakkrit; Chen, Lei; Shontz, Kimberly; Lewis, Sarah; Sahenk, Zarife
Abstract Neurotrophin 3 (NT-3) has well-recognized effects on peripheral nerve and Schwann cells, promoting axonal regeneration and associated myelination. In this study, we assessed the effects of AAV.NT-3 gene therapy on the oxidative state of the neurogenic muscle from the TremblerJ (TrJ ) mice at 16 weeks post-gene injection and found that the muscle fiber size increase was associated with a change in the oxidative state of muscle fibers towards normalization of the fiber type ratio seen in the wild type. NT-3-induced fiber size increase was most prominent for the fast twitch glycolytic fiber population. These changes in the TrJ muscle were accompanied by increased phosphorylation levels of 4E-BP1 and S6 proteins as evidence of mTORC1 activation. In parallel, the expression levels of the mitochondrial biogenesis regulator PGC1α, and the markers of glycolysis (HK1 and PK1) increased in the TrJ muscle. In vitro studies showed that recombinant NT-3 can directly induce Akt/mTOR pathway activation in the TrkC expressing myotubes but not in myoblasts. In addition, myogenin expression levels were increased in myotubes while p75NTR expression was downregulated compared to myoblasts, indicating that NT-3 induced myoblast differentiation is associated with mTORC1 activation. These studies for the first time have shown that NT-3 increases muscle fiber diameter in the neurogenic muscle through direct activation of mTOR pathway and that the fiber size increase is more prominent for fast twitch glycolytic fibers.